Dealkalization of Red Mud by Carbide Slag and Flue Gas. Issue 3 (31st January 2018) - Wang, Xinke; Zhang, Yihe; Liu, Jingang; Hu, Pan; Meng, Ke; Lv, Fengzhu; Tong, Wangshu; Chu, Paul K.
Abstract : Red mud and carbide slag which are industrial waste materials from alumina and chlor‐alkali plants pose environmental risks due to the large production volume. However, reutilization has been limited due to their composition and structure and the large alkali concentration in red mud has hampered utilization of red mud. At the same time, flue gas produced during the process of coal firing is a major environmental threat causing greenhouse effects and fog haze. In this work, alkalis (Na2 O) in red mud were released by the alkali and acid methods and carbide slags and flue gas were utilized to remove alkalis from red mud. The effects of the reaction time, temperature, and solid‐to‐liquid ratio on dealkalization of red mud by carbide slag were studied. Flame absorption and X‐ray diffraction were employed to monitor the changes in the red mud before and after dealkalization. Under the optimal conditions, the residual Na2 O amount in the red mud after dealkalization using the carbide slag diminished to less than 3 wt%, whereas that of Na2 O dropped to less than 2 wt% using flue gas. The pH of the suspension is determined by the acid method. The hydroxysodalite (Na8 Al6 Si6 O24 (OH)2 ) structure in the initial red mud was destroyed and soluble sodium salts formed in the suspension can be easily replaced by carbide slag or flue gas reducing Na2 O. Abstract : Red mud (RM) and carbide slag are industrial wastes from alumina and chlor‐alkali plants. Alkalis (Na2 O) in red mud are removed by carbide slags and flue gas. The residual Na2 O amount in red mud after dealkalization using carbide slag diminishes to less than 3 wt%, while, the residual Na2 O diminishes to less than 2 wt% by flue gas.